Study of all-polymer-based waveguide resonant gratings and their applications for optimization of second-harmonic generation. (17th August 2015) - Luong, Mai Hoang; Nguyen, Thi Thanh Ngan; Nguyen, Chi Thanh; Ledoux-Rak, Isabelle; Lai, Ngoc Diep
Abstract: We investigated theoretically and experimentally the optical properties of all-polymer-based one-dimensional waveguide resonant gratings (WRGs) and their important applications for the optimization of second-harmonic generation (SHG). We first studied the basic theory of the resonant modes of a simple grating-coupled waveguide realized on a material possessing a low refractive index contrast. The optical properties of any WRG were numerically simulated by using the finite-difference time domain method, performed by commercial Lumerical software. The polymer-based surface relief gratings were fabricated on azopolymer Disperse Red 1-Poly-Methyl-Methacrylate (DR1–PMMA) thin films by using the two-beam interference method and mass transport effect. Their experimental reflection spectra measured as a function of incident light wavelength are in good agreement with the theoretical predictions. We then demonstrated a first application of such a polymer-based WRG for nonlinear optics. Thanks to the strong local electrical field in the WRG, due to a guided-mode resonance condition, the SHG signal of an infrared light beam was strongly enhanced by a factor of 25 as compared to the result obtained in a sample without a grating.